Association Between Emotional Intelligence and Relationship Building in Secondary-Level School Classrooms - Thapa, Yogendra; Yadav , Rajeswor (Education Quarterly, 2024)
This study examines the impact of emotional intelligence (EI) on students’ participation in relationship-building in secondary-level classrooms. A random sample of 486 students studying in grades 11 and 12 in Jhapa, Myagdi and Lamjung were selected through a random selection process. The Schutte Self-Report Emotional Intelligence Test (SSEIT) and a fivepoint Likert scale were used to measure the association of students’ emotional intelligence with relationship building. The results show that individuals with higher emotional intelligence have stronger academic relationships and fostered positivity, effort, and positive attitude, which led to academic growth, improved communication, and respectful conduct. It was concluded that emotional intelligence had positive and supportive relationships with academic performance. The study suggests that teachers need to raise their students’ emotional intelligence and foster more profound and meaningful relationships by introducing mindful activities, patience and self-awareness in their everyday lives.